2023
DOI: 10.1073/pnas.2305662120
|View full text |Cite
|
Sign up to set email alerts
|

A sub-10-nm, folic acid-conjugated gold nanoparticle as self-therapeutic treatment of tubulointerstitial fibrosis

Cecilia Ka Wing Chan,
Cheuk Chun Szeto,
Leo Kit Cheung Lee
et al.

Abstract: Nanomedicines for treating chronic kidney disease (CKD) are on the horizon, yet their delivery to renal tubules where tubulointerstitial fibrosis occurs remains inefficient. We report a folic acid-conjugated gold nanoparticle that can transport into renal tubules and treat tubulointerstitial fibrosis in mice with unilateral ureteral obstruction. The 3-nm gold core allows for the dissection of bio–nano interactions in the fibrotic kidney, ensures the overall nanoparticle (~7 nm) to be small enough for glomerula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 67 publications
0
3
0
Order By: Relevance
“…Ji et al developed a reduced glutathione-responsive NP-based drug delivery system to target activated cardiac fibroblasts, further in vivo study verified that the system improves the therapeutic efficacy of MI-induced cardiac fibrosis with lower systemic toxicity [ 126 ]. Another research demonstrated that 7 nm folic acid-conjugated gold nanoparticle can effectively inhibit renal fibrosis through targeting to renal tubule cells [ 127 ]. These results suggested that cell-type specific targeting therapy strategy may provide an effective treatment for organ fibrosis.…”
Section: Targeting P53 For Organ Fibrosis Therapymentioning
confidence: 99%
“…Ji et al developed a reduced glutathione-responsive NP-based drug delivery system to target activated cardiac fibroblasts, further in vivo study verified that the system improves the therapeutic efficacy of MI-induced cardiac fibrosis with lower systemic toxicity [ 126 ]. Another research demonstrated that 7 nm folic acid-conjugated gold nanoparticle can effectively inhibit renal fibrosis through targeting to renal tubule cells [ 127 ]. These results suggested that cell-type specific targeting therapy strategy may provide an effective treatment for organ fibrosis.…”
Section: Targeting P53 For Organ Fibrosis Therapymentioning
confidence: 99%
“…Au NPs can also inhibit other inflammatory signaling pathways. For instance, Chan et al introduced a sub-10-nm Au NP (~7 nm) coated with PEG and folic acid (FA) for kidney fibrosis 238 . The outcomes demonstrated that the Au NP was more effective in reducing tissue degeneration and inhibiting the p38α enzyme compared to standard Captopril therapy 238 .…”
Section: Anti-inflammatory Nanotherapeuticsmentioning
confidence: 99%
“…For instance, Chan et al introduced a sub-10-nm Au NP (~7 nm) coated with PEG and folic acid (FA) for kidney fibrosis 238 . The outcomes demonstrated that the Au NP was more effective in reducing tissue degeneration and inhibiting the p38α enzyme compared to standard Captopril therapy 238 . Shifting macrophage polarization from M1 to M2 plays key roles in resolving inflammation 239 .…”
Section: Anti-inflammatory Nanotherapeuticsmentioning
confidence: 99%